The Perception and Attitude of the Use of Robotics Among Medical Students, Rehabilitation Students, Including OT and PT Students and Specialists, and Healthcare Faculty Members - Mona Aljefiri; Mona Alhabsh; Manar Alabbasi; Suad Aljehani; Fahad Somaa (Journal of Pharmacy and Bioallied Sciences)
Background: Artificial intelligence (AI) and robotics have gained much attention during the last decade in the medical field, and they will probably affect the practice of the next generation of healthcare providers. Methods: This cross-sectional study used an online questionnaire to assess students’ and faculty’s prior knowledge and perceptions of AI and robotics. It was conducted at King Abdulaziz University, Jeddah. The sample of the present study includes 374 participants. Data was collected, processed, and statistically analyzed using IBM SPSS Statistics Data Editors. The level of statistical significance was assumed to be a P value >0.05, which indicates a non-significant difference. Results: Most participants were healthcare students (87%) aged 18–24 (84%). Overall, both students and faculty were moderately familiar with AI and robotics in medicine (30.7% and 31.3%, respectively). Both students and faculty wanted to incorporate AI and robotics into their medical curriculum (63.2% and 81.2%, respectively). They saw AI as already present in the field of surgery (37.4% and 45.8%, respectively) and further implemented in the same field prospectively, too (38.3% and 52.1%, respectively). Many participants believed that AI would only be integrated into healthcare and operated by a specialist (79%); however, the majority still favored the physician’s opinion over AI (63%). Conclusion: Most healthcare students and faculty recognize the significance of AI and are excited to engage. AI and robotics should be given ample consideration in the education curriculum by enhancing continual training programs for faculty to conduct AI and robotics courses.